Ionomics: PTFI Platform - Chaparro, Jacqueline M; Odenkirk, Melanie T; Prenni, Jessica E; Watkins, Steve; Brinkley, Sarah (2025)
The PTFI ionomics method quantifies the concentrations of 26 biologically important elements across a wide range of plant and animal foods. This method utilizes acid digestion to free all elements prior to their analysis by inductively coupled plasma-mass spectrometry (ICP-MS).